Effect of Bedding Systems on Hygiene and Milk Yield of Crossbred Dairy Cows (Indian Journal of Animal Production and Management, 2024)
In dairy cattle, bedding and its management contribute predominantly to the comfort of the cow, udder  health and milk quality. The aim of the study is to assess the effect of different bedding materials such  as concrete floor, rubber mats, coir pith and dried solid manure on hygiene and milk yield and in  crossbred dairy cows. Twenty-four crossbred cows with six animals in each group were selected for  the study for one lactation period spread over three different seasons. The control group (T1) was  maintained in concrete floor without any bedding material. In (T2) rubber mats of 1.2 m × 1.8 m ×  0.025m area were provided on concrete floor. In (T3) coir pith and (T4) dried solid manure (DSM) on  concrete floor was the bedding. The mean tail head, upper rear limb, ventral abdomen, udder and  lower rear limb hygiene score of the T1 group were higher than other groups, which indicated that  the cows became ‘dirty’ and the T3 group had lower score than others which denoted cows were  ‘very clean’ with significant difference (P
Keywords: Bedding systems; crossbred cows; hygiene; milk yield